Household Industry Business Analysis in Improving Family Revenues - Nel Arianty (Proceedings of AICS - Social Sciences, 2017)
To be able to compete every business the home industry must be able to prepare and have a strategy in order to produce a quality product. In addition, the home industry business must have a wide marketing network with the aim that the resulting product can be accepted by the market or consumers, have competent human resources, and have the capital. In addition, the household industry also always has the availability of raw materials to facilitate the production process produced. Thus, it is expected that small industries can increase family income or community income. Household industries are small and medium enterprises as the Central Bureau of Statistics states that small and medium enterprises are identical with small industries and home industries. The Central Bureau of Statistics classifies industries based on the number of workers, namely: (1) home industry with 1-4 workers; (2) small industries with workers 5-19 people; (3) medium industries with workers 20-99 people; (4) large industry with 100 or more workers.Revenue is the net acceptance of a person, whether in cash or in nature. Public income can be classified into two, namely: permanent income and transitory income